Increasing the attraction water velocity at fishway entrances : model and field experiments - Lindmark, Elianne; Green, Torbjörn; Gustavsson, Håkan; Lundström, Staffan (Luleå tekniska universitet, Strömningslära och experimentell mekanik, 2008)
When Atlantic salmon (Salmo salar) and sea trout (Salmo trutta) migrates upstream rivers they encounter obstructions such as hydropower plants. To increase the water velocity at the fish inlet of a fishway an attraction channel is used. The channel increases the velocity without using extra attraction water from the reservoir. Field experiments show that fish use the channel, and lab experiments show that the water velocity out of the channel is 38 % higher than the surrounding velocity and the increased velocity lasts for about 18 water depths down stream. Godkänd; 2008; Bibliografisk uppgift: CD-ROM; 20080825 (eliwas)